ENGLISH TEACHERS’ ASSESSMENT LITERACY IN CONDUCTING ASSESSMENT OF LEARNING - Nasution, Irwinsyah (Global Expert: Jurnal Bahasa dan Sastra, 2023)
Conducting assessment to students’ learning is one of responsibilities a teacher has to do. Therefore, it is necessary for teachers of English to have good assessment literacy in order to help teachers of English to construct and conduct good assessment instrument. Assessment literacy is teachers’ knowledge towards assessment and its implementation. This research was case study with descriptive method and aimed at finding out teachers’ assessment of learning literacy and its implementation. This research took place at SMA PGRI 2 Palembang and three teachers of English involved as participants. Interview, survey questionnaire, observation, and documentation were used in data collection. The results of study revealed that teachers of English were not familiar with the nature of assessment of learning, and teachers did not make use of their knowledge on assessment into practice. It is important for schools’ principals in particular and government in general to provide professional development to upgrade teachers’ assessment of learning literacy. Keywords: Teachers of English, assessment, assessment literacy, assessment of learning, assessment implementation